2005
DOI: 10.1159/000090515
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistologic Attempt to Find Carcinogenesis from Hepatic Progenitor Cell in Hepatocellular Carcinoma

Abstract: Aim: To clarify whether hepatocellular carcinoma (HCC) originates from hepatic progenitor cells and whether there is any correlation with the clinicopathologic factors of HCC, we reviewed 217 resected HCC specimens. Methods: Immunohistochemical examination of cytokeratin (CK) 7, CK19, CD34, and CD117 (c-KIT) was performed. Overexpression of CK7 and CK19 indicates differentiation from cholangiocellular and hepatic progenitor cells, while overexpression of CD34 and CD117 indicates hepatic stem cells. Fresh speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 54 publications
1
28
1
1
Order By: Relevance
“…However, previous studies also showed that about 10% of HCC with typical microscopic histologic features expressed CK19 (4,6). These CK19(+) HCC was found to behave more aggressively and had a worse outcome (4,(6)(7)(8)17). For example, Takano et al demonstrated that CK19(+) HCC exhibited higher invasiveness, metastatic potential, and poorer prognosis (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, previous studies also showed that about 10% of HCC with typical microscopic histologic features expressed CK19 (4,6). These CK19(+) HCC was found to behave more aggressively and had a worse outcome (4,(6)(7)(8)17). For example, Takano et al demonstrated that CK19(+) HCC exhibited higher invasiveness, metastatic potential, and poorer prognosis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells from HCC, as a result, should not express CK19 since they are supposed to originate from hepatocytes (16). However, previous studies also showed that about 10% of HCC with typical microscopic histologic features expressed CK19 (4,6). These CK19(+) HCC was found to behave more aggressively and had a worse outcome (4,(6)(7)(8)17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are increasing evidences that oval cells are the cellular targets for transformation in the development of HCC [7][8] . Oval cells might give rise to HCC as a result of the arrest of stem cell maturation [9] .…”
Section: Introductionmentioning
confidence: 99%